Rancang Bangun Wind Tunnel Spesifikasi Kecepatan Angin Rendah Terhadap Intensitas Turbulensi Aliran Udara - Ulum, Miftahul; Firmansyah, M. Adie; Riani, Novi Indah (Journal of System Engineering and Technological Innovation, 2024)
Air flow in the view of fluid mechanics phenomena is very important to study, for this reason many researchers have carried out experiments to prove that air flow has various characteristics in aerodynamics. In this research, researchers tried to create an air flow test tool, namely the Win Tunnel with low wind capacity, which is usually referred to as subsonic, as a learning medium for measuring laboratory capacity air flow. The method used in this research is experimental, where first a Subsonic Wind Tunnel design is created that can be used as a test tool, before the test tool can be used properly. In this study, the parameters used to determine the suitability of the tool were measuring the turbulence intensity value by placing positions in the test section, namely the front, middle and back of the test section location. by using variations in inverter fan rotation at frequencies of 15 Hz, 30 Hz and 45 Hz. The results of this research obtained a Mach Number value below 0.3, which proves that the Wint Tunnel made has the correct specifications, namely subsonic. From the results of positioning in the test section to obtain turbulence intensity, the results were 11.15%, 7.83%, and 12.5% at f15 Hz, 6.54%, 2%, and 2.76% at f30 Hz, while at f45 Hz the results were 2.47%, 0.87%, and 1.67%.. The best position for placing the pitot tube is in the middle of the test section